The Effectiveness of Key Performance Indicators (KPI)-Based Performance Assessment on Employee Performance with Job Satisfaction as a Mediating Variable - Herlina Agustik,Agus Wahyudi,Donni Apriyanto (Perkumpulan Dosen Program Hibah Indonesia, 2026)
Human resources are strategic assets that play an important role in determining the success of an organization in achieving goals and maintaining competitive advantage. (Dessler, 2020). One indicator of successful human resource management is the creation of optimal employee performance. (Wibowo, 2018). However, achieving high performance cannot be separated from various influencing factors, such as competence, motivation, work discipline, work environment, and leadership. Therefore, organizations need an effective performance appraisal system as an evaluation tool as well as a basis for managerial decision making. (Wibowo, 2018; Dessler, 2020). This study aims to examine the concept of employee performance, factors that influence performance, and analyze the implementation of a performance appraisal system in an organization through a case study at PT Bio Axion Healthindo. The method used was descriptive qualitative research with a literature review approach supported by case study analysis. Data were obtained from various literature sources related to human resource management and performance management, then analyzed to obtain an overview of the relationship between performance appraisal systems and employee performance improvement. Research results show that objective, transparent, and employee-development-oriented performance appraisals can increase employee productivity, motivation, and loyalty.(Wibowo, 2018; Khan et al., 2023). A case study at PT Bio Axion Healthindo showed that the implementation of unrealistic Key Performance Indicators (KPIs) can increase work stress and employee turnover. However, through more proportional adjustments to KPI targets and training and motivational support, the company succeeded in increasing job satisfaction, employee retention, and the effectiveness of performance achievement. These findings confirm that a fair, realistic, and sustainable performance appraisal system is a crucial factor in supporting employee performance improvement and overall organizational success.